Power Relations and Organizational Communication: A Source of Change (2019)
This article seeks to analyze the link between comunication and power, and stablish the effect that this link can have in organizational change. To reach the proposed aims, this article use the concept of power from a relational perspective, orientated towards the processes of comunication, looking his impact on the organizational processes. For this, it is used a descriptive methodology to clarify some definitions of the concepts of communication and power. Then, use an interpretive methodology to analyze their application in an organizational environment and its impact on human beings in the workplace.